2000
DOI: 10.1007/s11934-000-0034-0
|View full text |Cite
|
Sign up to set email alerts
|

Cryosurgery for prostate cancer: New technology and indications

Abstract: Patients diagnosed with prostate cancer who elect to pursue active treatment of their disease must choose among the many available treatment alternatives. Several treatment options now exist for similar-stage disease (clinical T1-3N0M0), including radical prostatectomy, external beam radiation, prostate brachytherapy (PB), and cryosurgical ablation of the prostate (CSAP). This article reviews the current role of CSAP in the treatment of clinically localized prostate cancer. CSAP has a role in the primary treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 33 publications
1
11
1
Order By: Relevance
“…4 patients (4.0%) reported mild incontinence requiring 1-2 pads per day after therapy, compared to the published rate of 4.4% [3]. The currently reported incidence of urethral sloughing in patients undergoing cryosurgery with the use of a urethralwarming catheter ranges from 0 to 15% [18][19][20], and urethral sloughing occurred in 5 of the 102 patients (4.9%) in the present series. No patients developed fistulae in the present series, consistent with the risk of \1% reported in a recent study [10].…”
Section: Discussioncontrasting
confidence: 50%
“…4 patients (4.0%) reported mild incontinence requiring 1-2 pads per day after therapy, compared to the published rate of 4.4% [3]. The currently reported incidence of urethral sloughing in patients undergoing cryosurgery with the use of a urethralwarming catheter ranges from 0 to 15% [18][19][20], and urethral sloughing occurred in 5 of the 102 patients (4.9%) in the present series. No patients developed fistulae in the present series, consistent with the risk of \1% reported in a recent study [10].…”
Section: Discussioncontrasting
confidence: 50%
“…Its use is mostly confined to lower-risk patients with a PSA G10 ng/ml [27,28]. The 5-year DFS range is from 23 to 74% [26,[29][30][31][32][33] with side effects including incontinence and erectile dysfunction in 960% of men [27]. A report from the Cryo On-Line Data (COLD) registry reported data for 279 patients who underwent salvage cryoablation.…”
Section: Role Of Cryotherapy and High-intensity Focused Ultrasoundmentioning
confidence: 99%
“…113 In addition, recent advances in cryotherapy, such as the use of smaller-gauge probes, argon-based probes (as opposed to traditional nitrogen-based probes), and improved imaging techniques have all lead to increased efficacy with a reduction in severe side effects. 114 This approach to the treatment of prostate cancer is also seen as a safe alternative for patients who are not good surgical candidates for radical prostatectomy. Several studies have demonstrated the advantages and disadvantages of focal therapy.…”
Section: Cryotherapy For Prostate Cancermentioning
confidence: 99%